Mood Disorders in High-Functioning Autism: The Importance of Alexithymia and Emotional Regulation - Morie, Kristen P. (J Autism Dev Disord, 2019)
Individuals with autism spectrum disorder (ASD) often have co-morbid anxiety and depression. Alexithymia and emotion regulation difficulties are commonly seen in individuals with ASD and in mood disorders. We hypothesized that alexithymia and emotional regulation would mediate the relationship between autistic features and anxiety/depression symptom severity. We collected data about emotional regulation, alexithymia, autistic symptoms and depression/anxiety in a sample of 64 young adults with ASD. We constructed two serial multiple mediator models, using autistic features as the independent variable and anxiety/depression symptoms as outcome variables. The serial relationship between alexithymia and emotional regulation mediated associations between autistic features and depression and anxiety, separately. The findings suggest that targeting alexithymia may benefit therapies designed to alleviate mood disorders in ASD.